Time base firing pulse delay control for improving single phase induction motor speed performance using fuzzy logic control - Hanafi, Dirman (2015)
This paper focuses on the fuzzy logic controller design for improving the single phase induction motor speed control performance. The controller strategy is done through phase angle control method. The phase angle is controlled by controlling the time base firing pulse angle delay of the triac. Based on experimental results, the fuzzy logic controller is a suitable controller to improve the single phase induction motor speed because it able to reduce the rise time, settling time, peak time and overshoot response to 0.10s, 0.17s, 0.29s and 0.09 % OS respectively. Then compares with the Proportional Integral Derivative (PID) controller responses, the fuzzy logic controller responses are better with the rise time (Tr), the settling time (Ts), the peak time (Tp) and the overshoot (% OS) are 0.08s, 0.08s, 0.05s and 0.004% smaller than PID controller.